Efficacy of Sambiloto Extracts, Andrographis paniculate, (Burm. F) in Inhibiting Diabetic Retinopathy Progression: An in Vivo Study: Oral Presentation - Experimental Study - Resident - Shariff, Muhammad Apriliandy; Amin, Ramzi; Ansyori, AK. (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesDiabetic retinopathy (DR) is one of diabetes mellitus complication and occurred in retinalmicrovascular. This study was aimed to investigate the efficacy of Sambiloto, Andrographispaniculate (A. paniculata) extract on glycemic profile, antioxidant and inflammatory cytokineparameters in diabetic rats, and phytochemical analysis of A. paniculata. MethodsA. paniculata extract (APE) was carried out by maceration with ethanol. Diabetes mellitus in Wistarmale rats was induced with streptozotocin. Retinal vessel diameters were estimated using a methodby Vucetic. Inflammatory cytokine and antioxidant parameters were evaluated in retinal tissue. Thealkaloid and flavonoid contents in extract were analyzed using thin layer chromatography method. ResultsFunduscopic examination presented some changes in the diameter of the blood vessels. The vesseldiameter in the diabetic retinopathy group with APE in concentration of 100 and 200 mg/kg BWgroups was significantly lower than in the DR group (p<0.05). The administration of APE in dosagesof 100 and 200 mg/kg BW showed reduced glutathione, SOD, and catalase levels compared to theDR group (p<0.05). ConclusionA. paniculata extract doses of 100 and 200 mg/kg BW improved diabetic retinopathy in rats throughhypoglycemic effects, antioxidant effects, and anti-inflammatory mechanisms.